Postprandial oxidative stress and gastrointestinal hormones: is there a link? - Malinska, Hana; Kahleova, Hana; Topolcan, Ondrej; Vrzalova, Jindra; Oliyarnyk, Olena; Kazdova, Ludmila; Belinova, Lenka; Hill, Martin; Pelikanova, Terezie (PloS one, 2014)
BACKGROUND: Abnormal postprandial elevation of plasma glucose and lipids plays an important role in the pathogenesis of diabetes and strongly predicts cardiovascular mortality. In patients suffering from type 2 diabetes (T2D) postprandial state is associated with oxidative stress, cardiovascular risk and, probably, with impairment of both secretion and the effect of gastrointestinal peptides. Evaluating postprandial changes of gastrointestinal hormones together with changes in oxidative stress markers may help to understand the mechanisms behind the postprandial state in diabetes as well as suggest new preventive and therapeutical strategies. METHODS: A standard meal test has been used for monitoring the postprandial concentrations of gastrointestinal hormones and oxidative stress markers in patients with T2D (n = 50) compared to healthy controls (n = 50). Blood samples were drawn 0, 30, 60, 120 and 180 minutes after the standard meal. RESULTS: Both basal and postprandial plasma concentrations of glucose and insulin proved to be significantly higher in patients with T2D, whereas plasma concentrations of ghrelin showed significantly lower values during the whole meal test. In comparison with healthy controls, both basal and postprandial concentrations of almost all other gastrointestinal hormones and lipoperoxidation were significantly increased while ascorbic acid, reduced glutathione and superoxide dismutase activity were decreased in patients with T2D. A positive relationship was found between changes in GIP and those of glucose and immunoreactive insulin in diabetic patients (p<0.001 and p<0.001, respectively) and between changes in PYY and those of glucose (p<0.01). There was a positive correlation between changes in GIP and PYY and changes in ascorbic acid in patients with T2D (p<0.05 and p<0.001, respectively). CONCLUSION/INTERPRETATION: Apart from a positive relationship of postprandial changes in GIP and PYY with changes in ascorbic acid, there was no direct link observed between gastrointestinal hormones and oxidative stress markers in diabetic patients. TRIAL REGISTRATION: ClinicalTrials.gov NCT01572402.
Keywords: Oxidative Stress; kyseliny mastné neesterifikované; oxidační stres; Humans; lidé středního věku; postprandiální období; Female; lipidy; lidé; Postprandial Period; Blood Glucose; Gastrointestinal Hormones; Diabetes Mellitus, Type 2; ženské pohlaví; Male; Middle Aged; Insulin; krevní glukóza; Lipids; Fatty Acids, Nonesterified; gastrointestinální hormony; mužské pohlaví; diabetes mellitus 2. typu; inzulin